2015
DOI: 10.3109/09537104.2015.1083544
|View full text |Cite
|
Sign up to set email alerts
|

Does “smoker’s paradox” exist in clopidogrel-treated Turkish patients with acute coronary syndrome

Abstract: Previously conducted studies revealed that smoking enhanced the efficacy of clopidogrel by increasing formation of the active metabolite (AM) from the prodrug through induction of the cytochrome CYP1A2. The expression of cytochrome enzymes depends on genotype and no data exists in literature conducted in Turkish patients comparing the clopidogrel responsiveness between active smokers and non-active smokers treated with clopidogrel. In this study, our aim was to investigate the clopidogrel responsiveness in clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…Enhanced clopidogrel response in smokers, defined as the smokers’ paradox, is not universal but was observed only in cytochrome P450 CYP1A2 A-allele carriers which indicate a genotype-dependent impact of smoking on clopidogrel responsiveness. [ 26 ] In our study, the existence of smokers’ paradox was also confirmed. Hypertension and diabetes were also considered to be other risk factors for HPR in recently conducted studies; however, in our study, we did not observe such kind of relationships.…”
Section: Discussionsupporting
confidence: 80%
“…Enhanced clopidogrel response in smokers, defined as the smokers’ paradox, is not universal but was observed only in cytochrome P450 CYP1A2 A-allele carriers which indicate a genotype-dependent impact of smoking on clopidogrel responsiveness. [ 26 ] In our study, the existence of smokers’ paradox was also confirmed. Hypertension and diabetes were also considered to be other risk factors for HPR in recently conducted studies; however, in our study, we did not observe such kind of relationships.…”
Section: Discussionsupporting
confidence: 80%
“…An analysis of the CROSS‐VERIFY (Measuring Clopidogrel Resistance to Assure Safety After PCI using VerifyNow) cohort not only found that smokers had significantly lower OTR that non‐smokers at baseline, but also that the level of OTR and frequency of high OTR in patients who quit smoking ( n = 77) rose significantly compared to persistent smokers at 1 month ( n = 105) . A slightly larger study ( n = 139 smokers) recently reported a lower rate of high OTR on clopidogrel among smokers compared to non‐smokers, and a separate study of patients with acute coronary syndrome found active smoking to be independently associated with lower risk of high OTR (OR 0.51, P = 0.02) . Further, our results are consistent with the PARADOX (The Influence of Smoking Status on the Pharmacokinetics and Pharmacodynamics of Clopidogrel and Prasugrel) study, which randomly assigned smokers ( n = 54) and nonsmokers ( n = 56) with stable coronary artery disease to clopidogrel 75 mg or prasugrel 10 mg for 10‐days, followed by a 14‐day washout and treatment cross‐over .…”
Section: Discussionmentioning
confidence: 98%
“…Cigarette smoking enhances the generation of the active metabolite of clopidogrel by inducing CYP1A2 activity . Several studies suggest that there may be a “smokers’ paradox,” as although smoking has many negative effects on cardiovascular health, smokers have greater platelet inhibition and lower rates of high OTR when compared to non‐smokers on clopidogrel . Consistent with this observation, the CLARITY—TIMI 28 (Clopidogrel as Adjunctive Reperfusion Therapy—Thrombolysis in Myocardial Infarction 28), CHARISMA (Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management, and Avoidance), and CURRENT‐OASIS 7 (Clopidogrel and Aspirin Optimal Dose Usage to Reduce Recurrent Events—Seventh Organization to Assess Strategies in Ischemic Symptoms) trials all suggested that the clinical benefit of clopidogrel might be greater in smokers compared to non‐smokers .…”
Section: Introductionmentioning
confidence: 92%
“…There is evidence to suggest that cigarette smoking is associated with improved responsiveness to clopidogrel, resulting in decreased clopidogrel on-treatment platelet reactivity. This is known as the ‘smokers paradox,’ the concept that active smokers treated with clopidogrel have more major adverse cardiovascular event (MACE) reduction compared with non-smokers treated with clopidogrel [ 84 ]. There is conjecture regarding the mechanism which underpins this phenomena, but one hypothesis is that smoking can induce enzymes of the P450 cytochrome system meaning that smokers are exposed higher levels of clopidogrel’s active metabolite, relative to non-smokers [ 85 , 86 , 87 , 88 ].…”
Section: The Evidence For Cyp2c19 Genotyping After Stroke or Tiamentioning
confidence: 99%